Novel phosphopantothenoylcysteine synthetase (PPCS) mutations with prominent neuromuscular features: Expanding the phenotypical spectrum of PPCS‐related disorders. Issue 9 (26th May 2022) - Lok, Aishin; Fernandez‐Garcia, Miguel A.; Taylor, Robert W.; French, Courtney; MacFarland, Robert; Bodi, Istvan; Champion, Michael; Josifova, Dragana; Raymond, Frances Lucy; Iuso, Arcangela; Jungbluth, Heinz; Milan, Anna; et al.
Abstract: Biallelic pathogenic variants in phosphopantothenoylcysteine synthetase, PPCS, are a rare cause of a severe early‐onset dilated cardiomyopathy with high morbidity and mortality. To date, only five individuals with PPCS ‐mutations have been reported. Here, we report a female infant who presented in the neonatal period with hypotonia, a necrotizing myopathy with intermittent rhabdomyolysis and other extracardiac manifestations before developing a progressive and ultimately fatal dilated cardiomyopathy. Gene agnostic trio genome sequencing revealed two rare variants in the PPCS [MIM: 609853] in trans, a previously reported pathogenic c.320_334del p. (Pro107_Ala111del) variant, and a c.613‐3C>G intronic variant of uncertain significance. Functional studies confirmed the likely pathogenicity of this variant. Our case provides clinical and histopathological evidence for an associated neuromuscular phenotype not previously recognized and expands the evolving phenotypic spectrum of PPCS ‐related disorders. We also performed a literature search of all previously published cases and summarize the common features.